The Pragmatic Elements of Stance and Engagement in “Dear Ijeawele” by Chimamanda Adichie - Olaleye, Taiwo Racheal; Farinde, Raifu Olanrewaju; Ogunrinde, Ebenezer Deji (Acta Universitatis Danubius. Communicatio, 2024)
This work examines the notions of stance and engagement in Chimamanda Adichie’s celebrated work, Dear Ijeawele. Adichie’s letter, serving as a guide for raising a feminist daughter, presents an opportune lens through which to analyze her stance and engagement with feminist themes. Drawing upon a comprehensive literature review, this study analyzes selected passages from Dear Ijeawele to identify Adichie’s position, beliefs, and attitudes towards gender equality and the empowerment of women. The paper also investigates the rhetorical strategies employed by Adichie to engage her readers, such as personal anecdotes and persuasive language. By situating the analyzed passages within the broader context of the book, the study evaluates the relationship between Adichie’s stance and engagement and the overall objectives of Dear Ijeawele. Comparative analysis with other feminist texts and Adichie’s previous works further enriches the exploration of her approach. The findings contribute to a deeper understanding of Adichie’s literary contributions and shed light on the impact of her writing in promoting feminist ideals and challenging societal norms.